Increase in Dye:Dendrimer Ratio Decreases Cellular Uptake of Neutral Dendrimers in RAW Cells - Vaidyanathan, Sriram (ACS Biomater Sci Eng, 2016)
Neutral generation 3 poly(amidoamine) dendrimers were labeled with Oregon Green 488 (G3-OG(n)) to obtain materials with controlled fluorophore:dendrimer ratios (n = 1–2), a mixture containing mostly 3 dyes per dendrimer, a mixture containing primarily 4 or more dyes per dendrimer (n = 4+), and a stochastic mixture (n = 4(avg)). The UV absorbance of the dye conjugates increased linearly as n increased and the fluorescence emission decreased linearly as n increased. Cellular uptake was studied in RAW cells and HEK 293A cells as a function of the fluorophore:dendrimer ratio (n). The cellular uptake of G3-OG(n) (n = 3, 4+, 4(avg)) into RAW cells was significantly lower than G3-OG(n) (n = 1, 2). The uptake of G3-OG(n) (n = 3, 4+, 4(avg)) into HEK 293A cells was not significantly different from G3-OG(1). Thus, the fluorophore:dendrimer ratio was observed to change the extent of uptake in the macrophage uptake mechanism but not in the HEK 293A cell. This difference in endocytosis indicates the presence of a pathway in the macrophage that is sensitive to hydrophobicity of the particle.